2008
DOI: 10.1007/s00421-008-0929-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and thermoregulatory effects of chronic bupropion administration in the heat

Abstract: Chronic BUP did not influence TT performance in 30 degrees C and subjects did not reach core temperature values as high as observed during the acute BUP study. It seems that chronic administration results in an adaptation of central neurotransmitter homeostasis, resulting in a different response to the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 22 publications
0
39
1
1
Order By: Relevance
“…The aim of this and previous studies (Watson et al 2005;Roelands et al 2008aRoelands et al , b, 2009) performed with the same protocol is to elucidate the possible underlying neurotransmitter-governed mechanisms of fatigue and thermoregulation during prolonged exercise in the heat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of this and previous studies (Watson et al 2005;Roelands et al 2008aRoelands et al , b, 2009) performed with the same protocol is to elucidate the possible underlying neurotransmitter-governed mechanisms of fatigue and thermoregulation during prolonged exercise in the heat.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol used in this study is identical to the protocol used previously (Watson et al 2005;Roelands et al 2008aRoelands et al , b, 2009, therefore we will address it brieXy. All subjects completed a preliminary maximal exercise test, a familiarization trial and 4 experimental trials.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Therefore, studies with specific effects on either the serotonergic or the dopaminergic systems have been conducted to elucidate the exact influence from either system (169,174,(220)(221)(222). However, in temperate environments a number of exercise studies with human subjects have failed to show any clear performance enhancing effects of elevating extracellular dopamine levels via dopamine reuptake inhibitors or through attempted alterations in cerebral serotonin levels via nutritional or medical manipulations (171,174,221,239,314).…”
Section: Dopaminementioning
confidence: 99%
“…Disturbance of brain homeostasis is difficult to accomplish and previously we clearly indicated that specific physiological reactions can occur, i.e., a marked difference in core temperature. Our previous human studies have shown that influencing dopaminergic re-uptake inhibition in the brain increased rectal temperature (Watson et al 2005;Roelands et al 2008Roelands et al , 2009). Methylphenidate, a potent dopamine reuptake blocker, increased rectal temperature already before the start of exercise in high ambient temperature, without any difference in skin temperature (Roelands et al 2008).…”
mentioning
confidence: 97%
“…This indicates that dopamine is capable of influencing human thermoregulation, without affecting peripheral factors such as skin temperature and sweat rate. Both acute and chronic bupropion administration increased core temperature during exercise in normal and high ambient temperature (Watson et al 2005;Roelands et al 2009). These findings indicate that dopaminergic neurotransmission is indeed able to influence human thermoregulation, presumably by an increased internal heat production.…”
mentioning
confidence: 99%